The quality of integrated reproductive health services: perspectives of clients in KwaZulu-Natal, South Africa - P Maharaj; C Munthree (AOSIS, 2005)
The focus of family planning programmes has shifted away from an emphasis on controlling fertility towards helping individuals achieve their reproductive goals. This article seeks to expand knowledge about the quality of integrated services from the perspective of clients at health facilities in KwaZulu-Natal. The results from 300 structured interviews with clients visiting health facilities found that overall quality of services was relatively high. However, the quality of services varied somewhat between rural and urban areas. Clients visiting urban health facilities reported greater satisfaction with services than clients visiting rural health facilities. The interviews with clients suggests that existing efforts to integrate services has had limited success. Clients were rarely offered an expanded range of services during their visit. In most cases, clients only received services for which they presented at the health facility.